Ethnobotanical documentation of Harike Wildlife Sanctuary (Ramsar Site), Punjab: A case study - Gautam, Sameer; Adhikari, Bhupendra Singh (Ethnobotany Research and Applications, 2023)
Background: Harike Wildlife Sanctuary (HWS) is a natural bank of medicinal plants and native flora; therefore regular monitoring is required to maintain such diversity. The objective of the present study is to document the medicinal plants used by local people settled around HWS besides to develop a systematic record of traditionally used medicinal plants. Methods: The data was collected with the help of a semi-structured questionnaire following the snowball sampling method. People with some knowledge of medicinal plants were targeted for gathering information. To confirm the plant availability and identification, various field surveys were conducted along with informants across the habitat types within Harike Wildlife Sanctuary. Besides the harvest time of different wild plants mentioned by informants and the database is prepared for useful medicinal plants. Results: A total of 85 species from 79 genera and 51 families were mentioned by informants for the treatment of 40 types of health ailments. Leaves (25% species) are the most used plant part and decoction (19 species) is the most used method for the preparation of the drug, while the most frequent administration of the drug is oral (85% species). The ethnobotanical indices like Use Value, Relative Importance and Fidelity Level (FL) of each species have been derived from the primary dataset. Conclusion: Even though the study area also has access to contemporary healthcare services, the study found that numerous species are utilized to treat a wide range of medical conditions. By creating an effective plan, the current study may help to preserve medicinal and aromatic plants. Keywords: Harike-wetland, Ethnobotany, Fidelity Level, Medicinal plants, Use Value, Punjab